INSTITUTIONAL AND LEGISLATIVE STRUCTURE OF WATER-QUALITY MANAGEMENT IN TURKEY - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1994)
This paper examines the administrative and legal structure of the wastewater sector in Turkey, identifying its shortcomings and their causes, and suggests solutions. The study begins by outlining the existing administrative and legal structure, then focusing on the areas where difficulties are faced and seeking solutions to them. Those administrative and legal facets which have produced improvements and/or function effectively have been analysed so as to provide examples for other areas. When examining the sector it was observed that problems common to every area are the failure to adequately define powers and responsibilities, the lack of coordination between sectoral organisations, and the fact that attention is generally concentrated on routine matters of secondary importance. The fact that numerous organisations share powers in the same ar ea causes confusion. Plurality also creates difficulties where enforcement is concerned. The existence of more than one set of regulations relating to the same area gives rise to loopholes. At the same time, unrealistic, and hence unenforceable standards undermine the effectiveness of sanctions. it has been concluded that a single organisation should be invested with the legal powers to lay down the principles of water management, that environmental courts should be set up to enforce legislation by means of sanctions; and that for this purpose existing legislation should be reexamined and revised as necessary and/or brought up to date.
Keywords: ADMINISTRATIVE AND LEGAL STRUCTURE; WATER QUALITY MANAGEMENT